1977
DOI: 10.1192/bjp.131.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Life Events and Illness: A Three Year Prospective Study

Abstract: In an investigation of the relation between life events (stressors) and illness, 87 medical students reported on a prospective basis their health and life events history over a three year period. There were a few positive findings, e.g. that subjects who reported more life events during the period also reported more illnesses during that period. Overall, however, the study showed a lack of statistically significant association between life events and illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Some have demonstrated that only in a small percentage of cases, the occur rence of certain events could explain the sub sequent onset of symptoms [11,17,18], while other authors [19][20][21][22] did not reveal any correlation between preceding events and later disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some have demonstrated that only in a small percentage of cases, the occur rence of certain events could explain the sub sequent onset of symptoms [11,17,18], while other authors [19][20][21][22] did not reveal any correlation between preceding events and later disease.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used is the Schedule of Recent Experience (Rahe et al, 1964). Subsequent life event lists have been variations with improvements (Fontana et d., 1972;Uhlenhuth et al, 1974;Tennant and Andrews, 1976;Schless et al, 1977;Wildman and Johnson, 1977;Dohrenwend et ul., 1978). Generally, the respondent decides whether an event has occurred or not, and he is not given an opportunity to supply the contextual details which are considered essential by the Bedford College Team.…”
Section: Part 2: Some Recent Advances In Methodsmentioning
confidence: 97%
“…Grant, Yager, Sweetwood, and Olshen (1982) found little evidence that life events were causally related to psychological symptoms. Other studies also found no as sociation between life events and disorder (Goldberg & Comstock, 1976;Schless, Teichman, Mendel, Weinstein, & Weller, 1977). As Brown (1981) noted, prospective designs, while they may have some advantage compared with retrospective designs, are not without deficits and do not address all the methodological complexities associated with research in the life events-illness area.…”
Section: Prospective Designsmentioning
confidence: 99%